Late Cenozoic Evolution of the northern North Sea and the North Sea Fan - Malla, Smita (2007)
Abstract The study was mainly focused on the development of the Late Cenozoic shelf outbuilding in the northern North Sea and offshore mid-Norway. Principles of seismic sequence stratigraphy were applied as a tool to understand the processes related to glacial dynamics in a marine setting and to analyze formation of the North Sea Fan and its relationship to the Norwegian Channel. In terms of seismic stratigraphical architecture, three distinct depositional regimes have been observed during the development of the Late Cenozoic shelf succession of the study area. These have been presented and discussed in megasequence context, which displays how glacial dynamics change basin geometry with respect to space and time. The prograding wedge megasequence I developed mainly due to grounded ice sheets during glacial maxima. The glacial derived sediments were sourced mainly from the uplifted southeastern mainland Norway due to tectonic activities just prior to the onset of extensive glaciation and continued uplift and erosion during glaciations. The huge sediment flux into the basin had consequences in changing the basin configuration; creating large accommodation space in the basin due to isostatic subsidence and shallowing basin margin due to infilling of the basin. This gave a unique situation for the further wedge growth. Continued climate deteriorating, the next extensive shelf edge glaciation started around 1.1 Ma which is very significant in terms of changing the basin geometry from progradation to aggradation. In the mean time Norwegian Channel was formed where ice stream flowed repetitively since 0.5 Ma. During those periods, a series of floating and grounding ice sheets were responsible for giving rise to the aggrading sequences as megasequence II. The second prograding wedge, megasequence NSF (North Sea Fan) developed as the result of fast flowing ice stream in the Norwegian Channel. The continued aggradation in the channel subsequently gave rise to progradation on the North Sea Fan since huge accommodation ...